Synthesis, DNA-Binding, Anticancer Evaluation, and Molecular Docking Studies of Bishomoleptic and Trisheteroleptic Ru-Diimine Complexes Bearing 2-(2-Pyridyl)-quinoxaline - Sofia Balou; Athanasios Zarkadoulas; Maria Koukouvitaki; Luciano Marchiò; Eleni K. Efthimiadou; Christiana A. Mitsopoulou (Bioinorganic Chemistry and Applications)
Herein, we report the synthesis and characterization of a bishomoleptic and a trisheteroleptic ruthenium (II) polypyridyl complex, namely, [Ru(bpy)2(2, 2′-pq)](PF6)2 (1) and [Ru(bpy) (phen) (2, 2′-pq)](PF6)2 (2), respectively, where bpy = 2,2′-bipyridine, phen = 1,10-phenanthroline, and 2, 2′-pq = 2-(2′-pyridyl)-quinoxaline. The complexes were characterized by elemental analysis, TGA, 1H-NMR, FT-IR, UV-Vis, emission spectroscopy, and electrochemistry. Their structures were confirmed by single-crystal X-ray diffraction analysis. Complexes 1 and 2 were crystalized in orthorhombic, Pbca, and monoclinic, P21/n systems, respectively. Various spectroscopic techniques were employed to investigate the interaction of both complexes with calf thymus DNA (CT-DNA). The experimental data were confirmed by molecular docking studies, employing two different DNA sequences. Both complexes, 1 and 2, bind with DNA via a minor groove mode of binding. MTT experiments revealed that both complexes induce apoptosis of MCF-7 (breast cancer) cells in low concentrations. Confocal microscopy indicated that 2 localizes in the nucleus and internalizes more efficiently in MCF-7 than in HEK-293.